Structural and optical properties of ZnS thin films deposited by RF magnetron sputtering - Hwang, Dong Hyun (Springer, 2012)
Zinc sulfide [ZnS] thin films were deposited on glass substrates using radio frequency magnetron sputtering. The substrate temperature was varied in the range of 100°C to 400°C. The structural and optical properties of ZnS thin films were characterized with X-ray diffraction [XRD], field emission scanning electron microscopy [FESEM], energy dispersive analysis of X-rays and UV-visible transmission spectra. The XRD analyses indicate that ZnS films have zinc blende structures with (111) preferential orientation, whereas the diffraction patterns sharpen with the increase in substrate temperatures. The FESEM data also reveal that the films have nano-size grains with a grain size of approximately 69 nm. The films grown at 350°C exhibit a relatively high transmittance of 80% in the visible region, with an energy band gap of 3.79 eV. These results show that ZnS films are suitable for use as the buffer layer of the Cu(In, Ga)Se(2 )solar cells.